WOMEN AND CHURCH LEADERSHIP REVISED: THE IMPLICATIONS OF A MISSIONAL ECCLESIOLOGY AND A THEOLOGICAL ANTHROPOLOGY - Leene, A. M. J. ca. 21. Jh. (Scriptura, 2010)
The position of women in church leadership positions is still a burning issue. A key aspect of the issue is sexual identity and its implication for women in church leadership structures. Changing contexts and shifting paradigms have led, amongst others, to a rediscovery of the role of the Trinity. This in turn led to new perspectives on ecclesiology, i.e. a missional ecclesiology, as well as new perspectives on a theological anthropology. The unity and diversity in the Trinity form the basis of human identity irrespective of sexuality. As such the church offices are understood in the light of the missio Dei and need both men and women in leadership.